TEACHER PROFESSIONAL DEVELOPMENT THROUGH IMMERSIVE TECHNOLOGY: AUGMENTED REALITU SIMULATIONS IN HYBRID TEACHER TRAINING - Ardi Azhar Nampira; Van Sok; Dara Vann; Widi Harto Purnomo (Yayasan Adra Karima Hubbi, 2025)
Traditional teacher professional development (PD) models often fail to equip educators with the high-stakes competencies needed for complex classroom management and adaptation in hybrid learning environments. This inadequacy contributes to high early-career attrition, creating a critical need for high-fidelity, scalable practice solutions that bridge the gap between theory and immediate action. This study aimed to assess the causal efficacy of integrating a standardized Augmented Reality (AR) simulation module into hybrid teacher training, quantifying its impact on specific high-stakes teaching competencies (e.g., de-escalation and non-verbal communication). A quasi-experimental, pretest-posttest control group design (N=80) was used over ten weeks. The Experimental Group engaged in continuous AR simulations, while the Control Group received traditional video training. Competency gains were objectively measured using a specialized rubric and analyzed via ANCOVA. The AR intervention demonstrated a highly significant main effect on competency gains (F=42.15, p < 0.001), resulting in a 20.2 point gain, substantially outperforming the 6.8 point gain from passive training. The AR-trained group achieved a 45-second faster De-escalation Time and a 35% higher score in Non-Verbal Cues, validating the technology’s ability to foster mastery of subtle, complex skills. The AR simulation model is a pedagogically superior and necessary infrastructural component for teacher PD, effectively overcoming the structural limitations of conventional training. Its success in providing objective, embodied, and highly realistic practice provides a new, scalable standard for certifying hybrid teaching competence and mitigating teacher attrition.